Endoscopic assisted powered adenoidectomy versus conventional adenoidectomy – a randomised controlled trial. Issue 4 (3rd May 2019) - Juneja, R; Meher, R; Raj, A; Rathore, P; Wadhwa, V; Arora, N
Abstract: Objective: To compare endoscopic assisted powered adenoidectomy with conventional curettage adenoidectomy. Methods: A randomised controlled trial was conducted at a tertiary care teaching hospital. Fifty patients with a symptom complex pertaining to adenoid hypertrophy and requiring adenoidectomy were chosen and divided into 2 groups of 25 each. Patients in group A underwent conventional curettage adenoidectomy and those in group B underwent endoscopic assisted powered adenoidectomy. Comparison was based on the parameters of surgical time, intra-operative bleeding, post-operative pain and completeness of adenoid removal. Results: The surgical time was significantly longer with the powered instrument. Mean blood loss was greater in the powered group, but was statistically insignificant. The powered procedure fared significantly better, with lower pain scores and more instances of complete tissue resection. Conclusion: A curved microdebrider blade can be used safely and precisely for adenoidectomy under endoscopic vision. It enables complete resection of adenoid tissue. This method also proves to be an excellent teaching aid.